Estudio de casos de problemas con la lecto-escritura y su incidencia en el rendimiento académico de los niños de 4to a 6to de E.G.B. de la escuela particular Mons. Ignacio Larrea Holguín, en el cantón Durán en el periodo 2015-2016 - Gavilánez Marcillo, Verónica María (2015)
Reading and writing are two processes and skills that humans develop from the very beginning of his student, but so are the same children who have difficulty acquiring these skills. This research aims to meet the learning problems that cause delay, and that causes children are frustrated, fearful, isolated from the group, not participatory, others prefer to say often "do not know" because they are not on par with their classmates……